Animal-Assisted Intervention in Speech-Language Pathology: Practical, Clinical, and Theoretical Considerations - Antonucci, Sharon M. (Seminars in Speech and Language, 2022)
Interest in animal-assisted interventions within the field of communication sciences and disorders is growing. As more clinicians become interested in engaging in animal-assisted therapy (AAT) and more researchers begin to study its potential benefits, it will be critical for all stakeholders to demonstrate knowledge of the standards and qualifications for service delivery as well as the challenges that must be met in developing an evidence base for clinical practice. This review highlights some of the foundational information relevant to AAT in the context of speech-language pathology.
Keywords: animal-assisted therapy; communication sciences and disorders; therapy animal-handler teams